Testing Practices of Primary School English Language Teachers - Hanapi, Mohamad (Universiti Malaysia Sarawak, (UNIMAS), 2009)
This study investigates the current testing practices of English Language Teachers' in primary school. This study involved 24 English language teachers who were teaching primary 4 and 5. This study focused on 6 aspects of testing practices. The first aspect was on the types of formal test conducted in school. The second aspect was the reasons carrying out the formal test. The third aspect was teachers' preparation of the test paper. The fourth aspect was conducting the test by teachers. The fifth aspect was marking and recording the test. The sixth aspect was what the teachers do with the test results. The research instrument used in this study was semi structured interview. The findings of the study show that the formal test conducted were semester test, monthly test, school based oral assessment, topical test and diagnostic test. The respondents also stated that they carried out the formal test to assess students' achievement, diagnose students' progress, evaluate teaching effectiveness and as information to stakeholders. The finding also revea.. d that tie teachers prefer to discuss and take turn in preparing the test paper. The teachers also practiced more on UPSR style as the students seated individually according to the name list either monthly or semester test. The tests carried out are also invigilated by the teachers. Some of the schools prepared the test schedule to invigilate the students. The teachers marked the objective paper manually. The students' record cards are monthly test report card, school based oral assessment card and semester tests report card and given to the parents to be signed. Apart from that, the finding indicates that the teachers analyzed the test result is as instructed by the district education office. From the test analysis, the officer will look at the performance of the students either decrease or increase. Overall, it revealed that the current testing practices among the English language teachers in primary school were very much influenced by the public eý. '. minat; nn (t'PSR) in terms of preparing rnd conducting tl. test.